Análisis preliminar de un protocolo para la evaluación de marcos deícticos (2013)
The aim of this study was to explore differences in the performance of deictic tasks presented in the protocol of McHugh, Barnes-Holmes y Barnes-Holmes (2004a) related to procedural variations that consisted of a group of participants exposed to the protocol in a face-to-face interview format, in contrast with another group exposed to the protocol in a computerized version. 63 participants (9 to 12 years old) were paired by gender, age and grade and were assigned to one of the conditions. The number of errors was calculated for each participant and age group in each of the deictic frames and levels of relational complexity and inter-subjects effects were estimated using a two-way ANOVA with age and version (face-to-face and computer) as the independent variables and trial type as the dependent variable. The effect of age was significant for reversed NOW-THEN relations and the effect of version for simple I-YOU and HERE-THERE relations. A trend to produce more errors across all trial types in the computerized version was identified. Findings are discussed in terms of procedural reliability and ecological validity of non automated strategies for the assessment of derived stimulus relations.Keywords: Relational Frame Theory, deictic frames, perspective-taking, face-to-face procedures, automated procedures